Establishment of Entrepreneurial Character Santri Based on Human Resources Management - Aulia Zahra Husnil Kamala; Silviana Pebruary (Journal of Management and Entrepreneurship Research, 2021)
Objective: This research analysis about management human resources for santri Pondok Pesantren Darul Falah Amtsilati to manage academic and business personality. Research Design & Methods: This research uses qualitative research methods with case study approach. The data source in this study is primary data by conducting in-depth interviews to the manager (academic & business) and santri Pondok Pesantren Darul Falah Amtsilati. And observations were made to observe directly about the state of Darul Falah Amtsilati boarding school. Data analysis techniques use source triangulation. Findings: The results of this study showed that in the formation of the character of boarding schools Darul Falah Amtsilati using methods of precision, planting discipline, habituation, creating a conducive atmosphere, as well as integration and internalization. From the formation of the entrepreneurial character has been done based on the character of Islamic human resource. Where shiddiq is taught with honesty, trust by emphasizing responsibility, tabligh conveys correctly, and fathonah is realized by the selection of santri based on criteria. Implications & Recommendations: The implication of the results of this study is that the pesantren has used Islamic resource principles in the recruitment and learning process but needs to be improved or perfected in the implementation of learning by creating special classes for business character building. The aim is to help develop the quality of productive pesantren business managers. Contribution & Value Added: The contribution of the results of this study is to provide input to pesantren in improving the quality of prospective Islamic resources who will become managers of productive business activities of pesantren.